Estudo reológico de chocolates elaborados com diferentes cultivares de cacau (Theobroma cacao L.) - Leite, Paula Bacelar (2013)
Chocolate can be defined as a suspension of solid particles (sugar, cocoa solids and milk solids) in a continuous fat phase, which contributes to the aroma, flavour and colour, besides giving form to the final product. The rheology of chocolates is measured during production using two parameters: the yield stress and the apparent viscosity (plastic), generally using the Casson model. The objective of this study was to rheologically evaluate chocolate formulations produced from different cocoa cultivars. The chocolate samples were formulated with 73.6% of cocoa, and analyzed for their lipid content, triacylglycerol profile, rheological tests and the maximum particle size. The chocolate obtained from the cultivar PH16 showed the lowest fat content (36.53 g.100 g–1), largest particle size (21 µm), highest yield stress (20.91 Pa), greater hysteresis area and more ample thixotropy, when compared to samples of chocolates from the cultivars SR162 and Conventional. The results of the rheological studies showed the interference of the fat content and particle size on the yield stress of the products.